The Norwegian curriculum in history and historical thinking: a case study of three lower secondary schools - Lisbeth Bergum Johanson (Acta Didactica Norge, 2015)
Abstract The didactics of history and the content of the curriculum and syllabi have changed over the years in order to make history more relevant for the students of today. It is important to provide students with “knowing what” knowledge in addition to “knowing how” knowledge in order to support and develop critical thinking and historical understanding. One way of promoting historical understanding is through introducing the concepts of historical thinking. However, studies show that history classes often promote teaching that is still quite traditional, using history books uncritically and without problematizing their truthfulness, which do not make students see how history is formed, nor how it can be important for the present and the future. The present article explores whether the concepts of historical thinking are encouraged and used in three different lower secondary schools in Norway today. The main sources of data are current history textbooks, teaching plans, tests and assignments. The findings of the study show that the concepts of historical thinking are not made clear and explicit enough in neither history books, plans nor tests. Furthermore, it seems like reproduction rather than reflection is focused on in many classrooms, making it difficult to develop a historical understanding. It is therefore suggested that both teachers and students learn and work thoroughly with the concepts of historical thinking.schools in Norway today. History books in use, plans, tests and assignments were considered important empirical information for the research question. The findings of the study show that the concepts of historical thinking are not clear enough neither in history books, plans nor tests. Furthermore, it seems like reproduction rather than reflections are practiced in many classrooms, making it difficult to get a historical understanding. To accomplish historical understanding it is suggested that both teachers and students learn and work thoroughly with the concepts of historical thinking.